The Drosophila Transcription Factor Dimmed Affects Neuronal Growth and Differentiation in Multiple Ways Depending on Neuron Type and Developmental Stage - Liu, Yiting; Luo, Jiangnan; Nässel, Dick R. (Frontiers in Molecular Neuroscience, 2016)
Growth of postmitotic neurons occurs during different stages of development including metamorphosis, and may also be part of neuronal plasticity and regeneration. Recently we showed that growth of post-mitotic neuroendocrine cells expressing the basic helix loop helix (bHLH) transcription factor Dimmed (Dimm) in Drosophila can be regulated by insulin/IGF signaling and the insulin receptor (dInR). Dimm is also known to confer a secretory phenotype to neuroendocrine cells and can be part of a combinatorial code specifying terminal differentiation in peptidergic neurons. To further understand the mechanisms of Dimm function we ectopically expressed Dimm or Dimm together with dInR in a wide range of Dimm positive and Dimm negative peptidergic neurons, sensory neurons, interneurons, motor neurons and gut endocrine cells. We provide further evidence that dInR mediated cell growth occurs in a Dimm dependent manner and that one source of insulin-like peptide (DILP) for dInR mediated cell growth in the CNS is DILP6 from glial cells. Expressing both Dimm and dInR in Dimm negative neurons induced growth of cell bodies, whereas dInR alone did not. We also found that Dimm alone can regulate cell growth depending on specific cell type. This may be explained by the finding that the dInR is a direct target of Dimm. Conditional gene targeting experiments showed that Dimm alone could affect cell growth in certain neuron types during metamorphosis or in the adult stage. Another important finding was that ectopic Dimm inhibits apoptosis of several types of neurons normally destined for programmed cell death. Taken together our results suggest that Dimm plays multiple transcriptional roles at different developmental stages in a cell type-specific manner. In some cell types ectopic Dimm may act together with resident combinatorial code transcription factors and affect terminal differentiation, as well as act in transcriptional networks that participate in long term maintenance of neurons which might lead to blocked apoptosis.